Global research trend of esophageal squamous cell carcinoma from 2012 to 2022: a bibliometric analysis - Zhang, Zehua; Leng, Zhuyun; Fang, Kang; Sun, Mingchuang; Li, Zhaoxing; Kang, Le; Chen, Tao; Xu, Meidong (Frontiers in Oncology, 2022)
Background: Esophageal cancer is currently a worldwide health problem. Esophageal squamous cell carcinoma (ESCC) is the most common subtype of esophageal cancer, and its treatment methods and therapeutic effects are relatively limited, so it also requires the unremitting efforts of basic and clinical researchers to overcome difficulties. Bibliometric analysis can help sort out global research trends and hotspots, but no bibliometric analysis of ESCC has been reported. Therefore, we performed this study to analyze the global trends and potential hotspots of ESCC to indicate future research directions. Methods: The articles related to ESCC research were collected from the WoS Core Collection SCI-EXPANDED database from 2012 to 2022. The article information was analyzed by BiblioShiny and VOSviewer. Results were presented as bar and network visualization to describe the current trend of ESCC research. Results: The global publication trend illustrated a strong growth in the ESCC research field (annual growth rate 11.4%) and the citation trend increased from an average of 2.98 citations per article per year in 2012 to an average of 3.84 citations per article per year in 2019. With the corresponding author’s country, China contributed the largest number (5,063 articles). The scholars from China and USA had the most collaboration (427 times). China had the largest number of institutions conducting ESCC research. Oncotarget, Oncology Letters and Annals of Surgical Oncology published the most articles, while Cancer Research, International Journal of Cancer and Journal of Clinical Oncology had the most local citations. Furthermore, the clinical research hotspots involved in the treatment of ESCC and the basic research hotspots involved in tumor malignancy phenotype have received the most attention in recent years. Conclusion: Our study demonstrated that the research of ESCC has developed rapidly in recent years, and the academic institutions in China have played decisive role in this field. Global research purpose is to find effective therapies against ESCC, so some emerging hotspots related to ESCC treatment, such as endoscopic therapy, chemoradiotherapy, immunotherapy, tumor microenvironment and epithelial-mesenchymal transition will receive more attention and develop rapidly in the future.